Värmebehandling av ekollon (Quercus robur L) och dess påverkan på grobarhet och vitalitet hos unga plantor - Norrby, Nils-Erik (SLU/Southern Swedish Forest Research Centre, 2018)
Regeneration of pedunculate oak, Quercus robur, is hampered due to uneven supplies of acorns, infectious fungi and a generally low germination percentage of acorns. Aerated steam treatment was tested on acorns collected in southeast Sweden in order to determine if this method improves germination. Aerated steam treatment is a method developed to disinfect seeds from pathogens through the use of aerated steam and is used commercially in seeds of rice, cereals and vegetables. Acorns subjected to aerated steam treatment were sown at a nursery and germination percentage and the vitality of plants were evaluated. The results show that aerated steam treatment performed with low energy intensity can significantly increase the germination percentage of acorns and does not affect the vitality of plants.